Differential Regional Vulnerability of the Brain to Mild Neuroinflammation Induced by Systemic LPS Treatment in Mice - Jung H; Lee H; Kim D; Cheong E; Hyun YM; Yu JW; Um JW (Dove Medical Press, 2022)
Hyeji Jung,1 Hyojeong Lee,1 Dongwook Kim,1 Eunji Cheong,2 Young-Min Hyun,3 Je-Wook Yu,4 Ji Won Um1 1Department of Brain Sciences, Daegu Gyeongbuk Institute of Science and Technology (DGIST), Daegu, 42988, Korea; 2Department of Biotechnology, College of Life Science and Biotechnology, Yonsei University, Seoul, 03722, Korea; 3Department of Anatomy and Brain Korea 21 PLUS Project for Medical Science, Yonsei University College of Medicine, Seoul, 03722, Korea; 4Department of Microbiology and Immunology, Institute for Immunology and Immunological Diseases, Brain Korea 21 PLUS Project for Medical Science, Yonsei University College of Medicine, Seoul, 03722, KoreaCorrespondence: Ji Won Um, Email jiwonum@dgist.ac.krBackground: Peripheral inflammation-triggered mild neuroinflammation impacts the brain and behavior through microglial activation. In this study, we performed an unbiased analysis of the vulnerability of different brain areas to neuroinflammation induced by systemic inflammation.Methods: We injected mice with a single low dose of LPS to induce mild inflammation and then analyzed microglial activation in 34 brain regions by immunohistochemical methods and whole-brain imaging using multi-slide scanning microscopy. We also conducted quantitative RT-PCR to measure the levels of inflammatory cytokines in selected brain regions of interest.Results: We found that microglia in different brain regions are differentially activated by mild, LPS-induced inflammation relative to the increase in microglia numbers or increased CD68 expression. The increased number of microglia induced by mild inflammation was not attributable to infiltration of peripheral immune cells. In addition, microglia residing in brain regions, in which a single low-dose injection of LPS produced microglial changes, preferentially generated pro-inflammatory cytokines.Conclusion: Our results suggest that mild neuroinflammation induces regionally different microglia activation, producing pro-inflammatory cytokines. Our observations provide insight into induction of possible region-specific neuroinflammation-associated brain pathologies through microglial activation.Keywords: neuroinflammation, microglia, inflammatory cytokines, lipopolysaccharide, regional vulnerability